Apoptosis in Skeletal Myocytes: A Potential Target for Interventions against Sarcopenia and Physical Frailty – A Mini-Review - Marzetti, Emanuele; Calvani, Riccardo; Bernabei, Roberto; Leeuwenburgh, Christiaan (Gerontology (Basel), 2012)
Background: Sarcopenia, the age-related loss of muscle mass and function, represents a relevant public health issue due to its high prevalence and detrimental consequences. While the exact mechanisms underlying the pathogenesis of sarcopenia are not clear, growing experimental evidence indicates that progressive myonuclear elimination over the course of aging via an apoptosis-like process may represent a converging mechanism through which muscle atrophy and loss of physical function develop. Notably, the proapoptotic environment taking place in aged muscle appears amenable to interventions. Objective: We aimed at providing (1) an overview of signaling pathways of apoptosis relevant to sarcopenia, and (2) a review of the literature supporting myocyte apoptosis as a target for interventions against muscle aging. Methods: We summarized findings from studies focused on skeletal myocyte apoptosis as a mechanism in the development of sarcopenia and reports supporting myonuclear apoptosis as a target for interventions against age-related muscle loss. Results: Advanced age is associated with increased signaling through extrinsic and intrinsic apoptotic pathways in skeletal myocytes. In contrast, downregulation of myocyte apoptosis through calorie restriction, exercise training, hormonal supplementation, drugs (e.g. angiotensin-converting enzyme inhibitors, acetaminophen, antimyostatin antibodies), nutraceuticals or genetic interventions (e.g. PGC-1α overexpression) is linked with preservation of muscle integrity and improved physical performance in late life. Preliminary data also indicate that skeletal myocyte apoptotic signaling may be downregulated by compounds, such as resveratrol, with calorie restriction-mimicking properties. Whether exercise mimetics exert a similar effect has not yet been investigated. Conclusions: Available evidence suggests that targeting myonuclear apoptosis might provide novel and effective therapeutic tools to combat sarcopenia. Further research is required to definitely establish if downregulating myonuclear apoptosis is effective in maintaining muscle mass and function in late life, identify the most relevant apoptotic pathway(s) to target, and determine the optimal timing for intervening.